A new species of Elachistocleis Parker (Anura, Microhylidae) from the State of Acre, Northern Brazil - Nunes-De-Almeida, Carlos Henrique L.; Toledo, Luís Felipe (Zootaxa, 2012)
A new species of Elachistocleis is described from the municipality of Xapuri, state of Acre, northern Brazil. It distinguish-es from other species by the presence of an immaculate ventral coloration, SVL larger than 31 mm, and width head morethan 6.9 mm in adult males. Multivariate analysis based on external morphology also distinguishes the new species from the most morphologically similar species. The advertisement call is described and tadpoles remain unknown.